Social mediation and culture of peace (Revista de Investigaciones Universidad del Quindío, 2021)
Social relations in society involve a structural and dynamic process, in which interaction creates situations of coexistence, but also of differences, conflict or violence between people. The community, in addition to being a geographical space, configures social, cultural elements, own and shared interests, to understand, attend and mitigate situations of a conflictive nature in the community, social mediation represents a mechanism that contributes to a process of the culture of peace, starting from, integrating and developing basic aspects of the aforementioned mechanism, which implies developing or increasing in the members of the community strategies of dialogue, communication and participation in decision-making as well as managing and resolving conflicts. This document identifies basic elements of social mediation associated with the culture of peace, to contemplate the exercise of dialogue and communication between the members of a community, creating progressive scenarios of plurality and well-being.
Keywords: community; dialogue; prevention